El nuevo regionalismo y el Consejo de Defensa Suramericano - Serbin Pont, Andrei [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Southamerican Defense Council (CDS) is one of the most recent regional initiatives aimed at fostering defense integration in South America. It arises in the context of a multilateral organization of regional reach, UNASUR, that exemplifies many of the distinctive characteristics of the integration processes of the postliberal and/or posthegemonic regionalism period. The CDS aims at consolidating a series of objectives in matters of defense that correspond with this phase of regionalism, breaks traditional paradigms of importing and/or imposing extraregional models and seeks to implement solutions based on regional idiosyncrasy. In the framework of the creation of the CDS we analyze the integration mechanisms in matters of defense and the structures being developed in South America in the context of regional and subregional experiences that impact on the configuration of this particular council.

O Conselho de Defesa Sul-americano (CDS) é uma das iniciativas regionais mais novas para fomentar a integração em defesa na América do Sul. Ele surge no marco de um organismo multilateral de alcance regional, a UNASUR, que exemplifica muitas das características distintivas dos processos de integração do regionalismo pós-liberal e pós-hegemônico. O CDS aponta a consolidar uma série de objetivos em matéria de defesa correspondentes com esta etapa do regionalismo, que quebra com paradigmas tradicionais de importação e/ou imposição de modelos extra-regionais e procura implementar soluções próprias baseadas na idiossincrasia regional. No marco da criação do CDS analisamos os mecanismos de integração em matéria de defesa e as estruturas que estão sendo desenvolvidas em América do Sul no contexto das experiências regionais e sub-regionais que incidem na configuração particular deste conselho.

El Consejo de Defensa Suramericano (CDS) es una de las iniciativas regionales más recientes para fomentar la integración en defensa en América del Sur. Surge en el marco de un organismo multilateral de alcance regional, UNASUR, que ejemplifica muchas de las características distintivas de los procesos de integración del regionalismo postliberal y/o posthegemónico. El CDS apunta a consolidar una serie de objetivos en materia de defensa correspondientes con esta etapa del regionalismo, que quiebra con paradigmas tradicionales de importación y/o imposición de modelos extra regionales y busca implementar soluciones propias basadas en la idiosincrasia regional. En el marco de la creación del CDS analizamos los mecanismos de integración en materia de defensa y las estructuras que se están desarrollando en América del Sur en el contexto de experiencias regionales y subregionales que inciden sobre la configuración particular de este consejo.
Keywords: União de Nações Sul-Americanas; Segurança internacional; Cooperação internacional; América do Sul - Defesa; International cooperation